2022
DOI: 10.3389/fphar.2022.930832
|View full text |Cite
|
Sign up to set email alerts
|

Phaseolus vulgaris extract ameliorates high-fat diet-induced colonic barrier dysfunction and inflammation in mice by regulating peroxisome proliferator-activated receptor expression and butyrate levels

Abstract: Obesity is a health concern worldwide, and its onset is multifactorial. In addition to metabolic syndrome, a high-fat diet induces many deleterious downstream effects, such as chronic systemic inflammation, a loss of gut barrier integrity, and gut microbial dysbiosis, with a reduction of many butyrate-producing bacteria. These conditions can be ameliorated by increasing legumes in the daily diet. White and kidney beans (Phaseolus vulgaris L.) and their non-nutritive bioactive component phaseolamin were demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It is worth noting that hepatic gene expression of CPT‐1, PPAR‐α, and PPAR‐γ were strengthened in HFD‐group compared with NCD‐group, which did not show exactly the same trend as in WAT, and these results are not consistent with several recent studies. [ 69,70 ] These findings may be subject to hepatic homeostasis of fatty acid catabolism. [ 71 ] In fact, liver PPAR‐α is essential for overall fatty acid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that hepatic gene expression of CPT‐1, PPAR‐α, and PPAR‐γ were strengthened in HFD‐group compared with NCD‐group, which did not show exactly the same trend as in WAT, and these results are not consistent with several recent studies. [ 69,70 ] These findings may be subject to hepatic homeostasis of fatty acid catabolism. [ 71 ] In fact, liver PPAR‐α is essential for overall fatty acid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…As the effects of WKBE were attenuated after 4 months intervention compared with after 2 months, the authors concluded that this was likely due to gradual diminished improvements to the gut microbiota (Feng et al, 2022), suggesting that supplementation duration may be important. Most of the evidence in relation to the potential effects of WKBE on the gut microbiota comes from a small number of studies in animal models which suggest beneficial effects on gut microbiota composition and SCFA concentrations (Song et al, 2016; Neil et al, 2019; Shi et al, 2020; Wang et al, 2021; Avagliano et al, 2022). Most of these have explored the role of the gut microbiota as an underlying mechanism for the effects of WKBE in models of obesity or metabolic syndrome and are summarised in our previous review (Nolan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…of studies in animal models which suggest beneficial effects on gut microbiota composition and SCFA concentrations (Song et al, 2016;Neil et al, 2019;Shi et al, 2020;Wang et al, 2021;Avagliano et al, 2022). Most of these have explored the role of the gut microbiota as an underlying mechanism for the effects of WKBE in models of obesity or metabolic syndrome and are summarised in our previous review (Nolan et al, 2020).…”
Section: Long-term Use Associated With Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on isolated rat enterocytes have shown that 70 to 80% of oxygen utilization is due to β- oxidation of butyric acid, while the utilization of butyric acid by cells is higher than that of other metabolic substrates. [40] The importance of butyrate metabolism for colon-forming cells has also been demonstrated that germ-free mice can exhibit a situation of impaired metabolism and increase autophagy rates in the absence of butyrate for prolonged periods, and can be rescued by the bacteria of increasing butyric acid or producing butyric acid. [41] Hence, it is particularly important to understand the metabolic process of SCFAs and their fermented products in human body to assess their impact on liver, colorectal-related tumors, and metabolic damage.…”
Section: Gut Microecological Metabolitementioning
confidence: 99%